Comparison of Storage Stability and In Vitro Digestion of Rice Flour-Based Yogurt Alternatives Made with Lactobacillus rhamnosus Lgg to Milk-Based Yogurt - Anita Morris; Charles Boeneke; Joan M. King (Foods)
Production of plant-based products is still on the rise. There is a need for new plant-based dairy alternatives in the food market due to lactose intolerance, allergens to dairy and nuts and a rise in gluten-free products. Rice is a key source for these types of products because it is hypoallergenic. This study focused on the comparison storage stability and in vitro digestion of milk-based yogurt (MY) to yogurt alternatives (YA) made with four different rice flours. YAs and MY were prepared using L. delbrueckii and S. thermophilus for fermentation and L. rhamnosus (LGG) as a probiotic. Samples were stored refrigerated for up to 28 days and analyzed for titratable acidity, pH, color, syneresis, viscosity and bacterial counts every seven days. Probiotic survivability was tested under simulated gastric and intestinal conditions. YAs had lower syneresis than MY. There were few changes in color over time. Titratable acidity was lower in YAs (0.1 to 0.5%) than in MY (1%) while pH decreased in all samples during storage. Bacteria counts were stable throughout storage in all samples. MY had higher counts of LGG at the beginning of storage which significantly decreased during exposure to in vitro gastric conditions. Under in vitro intestinal conditions, both the white rice flour YAs and the MY retained the highest levels of LGG. This study indicated that it is possible for YAs made with rice flour to be stable overtime and with survivability of probiotic bacteria under gastric conditions.